A study of the photochemical behaviour and relaxation mechanisms of anti–syn isomerisation around quinazolinone –N–N bonds. Issue 42 (30th September 2022) - Hricovíni, Michal; Asher, James R.; Hricovíni, Miloš
Abstract : High-resolution NMR experiments revealed that differently substituted quinazolinone-based Schiff bases undergo anti to syn isomerisation on exposure to ultraviolet light in DMSO solution. Abstract : High-resolution NMR experiments revealed that differently substituted quinazolinone-based Schiff bases undergo anti to syn isomerisation on exposure to ultraviolet light in DMSO solution. The degree anti to syn conversion varied significantly upon substitution (between 5% and 100%) and also showed two noteworthy features: that relaxation back to the anti -form goes far faster (by at least 3 orders of magnitude) when the C6 rings B and C have ortho -OH substituents, and that relaxation can also be significantly sped up by addition of acid. Two possible mechanisms explaining the differences in relaxation process have been proposed: (I) the interaction of the azomethine hydrogen with the carbonyl oxygen results in slower reversion to the anti -form and/or (II) suppression of conjugation of the N3 lone pair with the NCH double bond by protonation and/or internal H-bonding. Both of these mechanisms have been analysed theoretically.